2013
DOI: 10.1080/03650340.2012.748984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle-size distribution on wind erosion rate and soil erodibility

Abstract: Wind erosion is a serious problem, especially in arid and semi-arid regions. This study was conducted to assess the effects of wind speed as well as soil particle-size distribution on erosion rate (ER) using a wind tunnel. For this purpose, two clay loam soil samples (C2 and C10) in addition to a sandy clay loam (S2) were exposed to different wind velocities of 2, 9 and 18 m s 71 . The result showed that erosion rate increased significantly with increasing wind speeds. In addition, a critical diameter of 0.84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Since most soils of arid and semiarid regions are low in organic carbon (Zamani and Mahmoodabadi, 2013;Cerdà et al, 2014;Tejada and Benítez, 2014), the application of organic amendments, such as animal manure, crop residues, and municipal solid waste (MSW) compost provides a management strategy to compensate for the depletion of SOC in these soils (Bronick and Lal, 2005;. Previous studies demonstrated positive changes in several soil physical, chemical and biological properties after the addition of organic amendments to the soil (Ferreras et al, 2006;Brevik, 2012;Eibisch et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Since most soils of arid and semiarid regions are low in organic carbon (Zamani and Mahmoodabadi, 2013;Cerdà et al, 2014;Tejada and Benítez, 2014), the application of organic amendments, such as animal manure, crop residues, and municipal solid waste (MSW) compost provides a management strategy to compensate for the depletion of SOC in these soils (Bronick and Lal, 2005;. Previous studies demonstrated positive changes in several soil physical, chemical and biological properties after the addition of organic amendments to the soil (Ferreras et al, 2006;Brevik, 2012;Eibisch et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…It was air dried and then passed separately through 2 and 4.75 mm sieves. Two soils with different maximum aggregate sizes were provided (Zamani and Mahmoodabadi, 2013), named D max 2 mm and D max 4.75 mm. Note there were no primary particles coarser than 2 mm in the soils because the original soil was collected from agricultural land.…”
Section: Soil Preparation and Characteristicsmentioning
confidence: 99%
“…were estimated as 950 g m -2 min -1 for the sandy soil (particle size of 2 mm), 175 g m -2 min -1 for the cultivated soil (particle size of 2 mm), and 28 g m -2 min -1 for the cultivated soil (particle size of 10 mm) (Zamani, Mahmoodabadi, 2013). Due to a very small mean weight diameter of the soil used in that study, the results shown in Figure 3 are lower than those of that study.…”
Section: Resultsmentioning
confidence: 99%
“…After each run, the sediment was collected; oven dried at 105°C, and weighed on a balance. To obtain the wind erosion rate (g m -2 h -1 ), the mass of the sediment (g) was divided by the test area (m 2 ) and event duration (h) (Zamani, Mahmoodabadi, 2013). Measurements were made once after one day from tillage in both years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation